Thirty Years of Shareholder Rights and Firm Value - CREMERS, MARTIJN; FERRELL, ALLEN (Journal of Finance, 2014)
ABSTRACT This paper introduces a new hand‐collected data set that tracks restrictions on shareholder rights at approximately 1,000 firms from 1978 to 1989. In conjunction with the 1990 to 2006 IRRC data, we track shareholder rights over 30 years. Most governance changes occurred during the 1980s. We find a robustly negative association between restrictions on shareholder rights (using G‐Index as a proxy) and Tobin's Q . The negative association only appears after judicial approval of antitakeover defenses in the 1985 landmark Delaware Supreme Court decision of Moran v. Household . This decision was an unanticipated exogenous shock that increased the importance of shareholder rights.